CHARISMATIC LEADERSHIP AND WORK MOTIVATION ON PERFORMANCE THROUGH JOB SATISFACTION OF REGIONAL SECRETARIAT EMPLOYEES IN BURU SELATAN REGENCY - Zacharias, Tehubijuluw (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to analyze the mediating effect of job satisfaction in influencing charismatic leadership and work motivation on employee performance. Sampling in this study was 35% of the existing population, namely 151 employees so that the sample was 53 employees at the Regional Secretariat of South Buru Regency. Data were analyzed by path analysis. The results showed that job satisfaction mediates the effect of charismatic leadership and motivation on performance.